Factors associated with Myopia among Children at Eye Hospital Kathmandu - Bista, Beenu; Shrestha, Soni; Gyawali, Bipanda (Journal of Manmohan Memorial Institute of Health Sciences, 2016)
Myopia is the most prevalent refractive error among the children leading to blindness. The prevalence rate is increased since few years back due to increase in modern technologies and mode of study among children. This descriptive cross sectional study aims to explore factors contributing to myopia among children visiting refractive clinic/refractive department of Nepal Eye Hospital. Non probability purposive sampling method and 206 children were used for this study. Structured questionnaire were used along with the children and their parents. Chi-square test was used for finding the association with the contributing factors. The study population varies between the ages of 5 to 17 years with the mean age±12 and mostly affecting the children above 10 years. Myopia is significantly associated with religion, ethnicity, heredity, parent’s level of education. Income status of family, reading at dim light is significantly associated with myopia as p-value is <0.0001. Myopia in children attending refractory OPD of Nepal Eye Hospital was associated with heredity, socio-economic status and level of education of parent; continue reading, additional classes, watching video/ television, using computer or cell phone, sports (football, cricket), dim light and not associated with residential area, type of school, night lightness, dietary pattern and ocular hygiene; therefore parents along with children and teachers should be given awareness program about early screening and its preventive measures. Journal of Manmohan Memorial Institute of Health Sciences Vol. 2 2016 p.61-69